2017
DOI: 10.3168/jds.2016-12506
|View full text |Cite
|
Sign up to set email alerts
|

Use of calcitriol to maintain postpartum blood calcium and improve immune function in dairy cows

Abstract: Our objectives were to determine the effects of an injectable formulation of calcitriol on mineral metabolism and immune function in postpartum Holstein cows that received an acidogenic diet prepartum to minimize hypocalcemia. In experiment 1, cows within 6 h of calving received calcitriol (0, 200, or 300 μg) to determine the dose needed to increase plasma concentrations of Ca; 300 μg was sufficient to sustain Ca for at least 3 d. In experiment 2, multiparous cows were assigned randomly to receive only vehicle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 39 publications
1
48
0
Order By: Relevance
“…Therefore, it is suggested that the increased blood concentrations of 25-hydroxyvitamin D 3 and 1,25-dihydroxyvitamin D 3 stimulated innate immune cell function, which is paramount for prevention of certain periparturient diseases in cattle. A similar positive response in neutrophils has been demonstrated when cows receive a subcutaneous dose of calcitriol immediately after calving (Vieira-Neto et al, 2017). Also, the high concentrations of 25-hydroxyvitamin D 3 from feeding CA might have acted directly on vitamin D receptor (Lou et al, 2010), thereby stimulating activity of immune cells independently of systemic changes in 1,25-dihydroxyvitamin D 3 or cellular synthesis of 1,25-dihydroxyvitamin D 3 and the resulting autocrine effects.…”
Section: Discussionmentioning
confidence: 57%
“…Therefore, it is suggested that the increased blood concentrations of 25-hydroxyvitamin D 3 and 1,25-dihydroxyvitamin D 3 stimulated innate immune cell function, which is paramount for prevention of certain periparturient diseases in cattle. A similar positive response in neutrophils has been demonstrated when cows receive a subcutaneous dose of calcitriol immediately after calving (Vieira-Neto et al, 2017). Also, the high concentrations of 25-hydroxyvitamin D 3 from feeding CA might have acted directly on vitamin D receptor (Lou et al, 2010), thereby stimulating activity of immune cells independently of systemic changes in 1,25-dihydroxyvitamin D 3 or cellular synthesis of 1,25-dihydroxyvitamin D 3 and the resulting autocrine effects.…”
Section: Discussionmentioning
confidence: 57%
“…In fact, the ratio of 24,25-dihydroxyvitamin D 3 to 25-hydroxyvitamin D 3 increased 3-fold pre-and postpartum in cows fed CA compared with cows fed CH, supporting the concept of induction of 24-hydroxylase abundance or activity as the supply of 25-hydroxyvitamin D 3 increased. Abundance of the 24-hydroxylase enzyme increases by 1,25-dihydroxyvitamin D 3 via vitamin D response elements in the CYP24A1 gene promoter (Pike, 2011), and administration of 1,25-dihydroxyvitamin D 3 to cows immediately after calving increased concentrations of 24,25-dihydroxyvitamin D 3 (Vieira-Neto et al, 2017); thus, increased 24,25-dihydroxyvitamin D 3 concentrations in calcidiol-fed cows may also be caused by increased 24-hydroxylase abundance. Differences in concentrations of 24,25-dihydroxyvitamin D 3 between parity groups suggest that as cows age, activity of 24-hydroxylase increases, perhaps because of uncoupling CYP24A1 with age that might contribute to the impairment of vitamin D metabolism that has been shown in old dairy cows (Horst et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Martinez et al (2018a) reported a tendency for increased postpartum BHB for cows fed 3 mg 25(OH)D prepartum compared with cows fed 3 mg vitamin D 3 . Vieira-Neto et al (2017) also reported that a one-time subcutaneous injection of 300 μg of 1,25(OH) 2 D 3 to postpartum cows increased serum BHB compared with placebo injection. Postpartum oral administration of a single Ca bolus increased serum BHB in cows at low risk for metritis (Martinez et al, 2016); however, the increased serum Ca from the oral Ca bolus was transient, and the elevated BHB concentrations of Ca-treated cows were present when serum Ca was lesser than placebo cows.…”
Section: Vitamin D Nutrition and Physiologymentioning
confidence: 93%